An exploration of smokeless tobacco product nucleic acids: a combined metagenome and metatranscriptome analysis - Tyx, R. E. (Appl Microbiol Biotechnol, 2019)
Smokeless tobacco (ST) products are used worldwide and are a major public health concern. In addition to harmful chemicals found in these products, microbes found in ST products are believed to be responsible for generating harmful tobacco-specific nitrosamines (TSNAs), the most abundant carcinogens in ST. These microbes also contribute endotoxins and other pro-inflammatory components. A greater understanding of the microbial constituents in these products is sought in order to potentially link select design aspects or manufacturing processes to avoidable increases in harmful constituents. Previous studies looked primarily at bacterial constituents and had not differentiated between viable vs nonviable organisms, so in this study, we sought to use a dual metatranscriptomic and metagenomic analysis to see if differences exist. Using high-throughput sequencing, we observed that there were differences in taxonomic abundances between the metagenome and metatranscriptome, and in the metatranscriptome, we also observed an abundance of plant virus RNA not previously reported in DNA-only studies. We also found in the product tested, that there were no viable bacteria capable of metabolizing nitrate to nitrite. Therefore, the product tested would not be likely to increase TSNAs during shelf storage. We tested only a single product to date using the strategy presented here, but succeeded in demonstrating the value of using of these methods in tobacco products. These results present novel findings from the first combined metagenome and metatranscriptome of a commercial tobacco product. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00253-019-10232-3) contains supplementary material, which is available to authorized users.